Central nervous system high-grade neuroepithelial tumor with BCOR alteration: case report - Ughini Crusius, Marcelo; Santiago, Pablo; Delazeri, Marco Antonio; Kegler, Maria Eduarda; Da Silva, Rodrigo Alberton; Lima, Matheus Henrique Benin; Spannenberg, Orly Matheus Gampert; Belato Teixeira, Julia (Clinical and Biomedical Research, 2022)
Central nervous system high-grade neuroepithelial tumors with BCOR alteration are a rare disease. Currently, there are only 24 cases reported in the literature. They are characterized by a change involving the BCOR gene and have a poor prognosis. Studies are needed to improve the current therapy and outcomes of these neoplasms. This case report describes the clinical history of a patient with this pathology and aims to contribute to the current knowledge about this new entity.